Evaluación del nivel de desempeño profesional de los egresados del instituto superior pedagógico José Gabriel Vega Betancourt de la ciudad de Santa Rosa y diseño de un sistema de seguimiento, a fin de verificar las competencias profesionales en el campo ocupacional, del período lectivo 2010- 2012. - Mena Ramírez, Medardo Abelino (2014)
Ecuador is the great challenge of strengthening its education system as fundamental to the social development of peoples through the competitiveness and improving the quality of life of citizens pillar. As part of the citizen's revolution , the rule establishes the National Plan for Good Living where one of their policies is reflected to the same quality education that is performed based on quality standards and evaluation of educational skills . In the above context is the culmination of the work in teacher training colleges nationwide to hold this work at the National University of Education , an organization that meet quality standards .